Growth and productivity of vegetables under Anthocephalus cadamba based silvihorticultural system - Rajalingam, G.V.; Parthiban, K.T.; Sivakumar, K.; Divya, M.P. (Indian Journal of Agroforestry, 2020)
An experiment was conducted to develop a suitable Anthocephalus cadamba based silvihorticultural system for higher productivity in Western zone of Tamil Nadu. Tomato ( Lycopersicon esculentum), egg plant (Solanum melongena), okra (Abelmoschus esculentus), cluster beans (Cyamopsis tetragonaloba) and vegetable cowpea (Vigna unguiculata) were intercropped in 2 years old A. cadamba. Results revealed that the growth and yield of intercrops were reduced under intercropping compared to sole cropping. Among the test crops, tomato was most affected and vegetable cowpea was the least affected. However the benefit cost ratio was highest for tomato (2.46) due to the higher productivity and lowest for cluster beans (2.19). Growth of A. cadamba was also influenced due to intercropping with vegetable cowpea and cluster beans. The increment in tree height, DBH and collar diameter of A. cadamba was highest with vegetable cowpea intercropping (34.4 %, 20.7 % and 18.3 % increase over sole tree) and the lowest was observed with tomato (6.3 %, 8.7 % and 10.2 % increase over tree alone).